2013
DOI: 10.1088/0031-9155/58/9/2955
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of BCF plastic scintillation detectors

Abstract: We examined temperature dependence in plastic scintillation detectors (PSDs) made of BCF-60 or BCF-12 scintillating fiber coupled to optical fiber with cyanoacrylate. PSDs were subjected to a range of temperatures using a temperature-controlled water bath and irradiated at each temperature while either the dose was measured using a CCD camera or the spectral output was measured using a spectrometer. The spectrometer was used to examine the intensity and spectral distribution of scintillation light emitted by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 21 publications
9
65
1
Order By: Relevance
“…Corrections for energy-dependence can be applied as suggested in this article and by (Reniers et al 2012, Pittet et al 2013), and corrections for temperature and time-dependence can be applied as suggested by Wootton and Beddar (2013), and the present study, respectively. Also, Martinez et al (2015) showed that the scintillation signal of YVO 4 :Eu changes by 0.01%/°C under 60 Co irradiation.…”
Section: Discussionmentioning
confidence: 96%
“…Corrections for energy-dependence can be applied as suggested in this article and by (Reniers et al 2012, Pittet et al 2013), and corrections for temperature and time-dependence can be applied as suggested by Wootton and Beddar (2013), and the present study, respectively. Also, Martinez et al (2015) showed that the scintillation signal of YVO 4 :Eu changes by 0.01%/°C under 60 Co irradiation.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, their small size allows them to be placed inside narrow BT catheters inserted in the tumor region, and real-time monitoring of the detector response facilitates online error detection. The response of ISDs to absorbed dose in water is, in contrast to that of PSDs, dependent on the photon energy spectrum (Rogers 2009), while both ISD and PSD responses exhibit temperature dependence (Edmund and Andersen 2007, Beddar 2012, Wootton and Beddar 2013, Buranurak et al 2013). However, the energy and temperature dependences can be corrected for with fairly straightforward methods (Wootton and Beddar 2013, Reniers et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because the output of some plastic scintillation detectors is temperature dependent (Beddar, 2012) (Wootton and Beddar, 2013), the OARtrac system was designed to automatically compensate for temperature when processing data, by means of empirical correction factors that are based on a user-entered temperature. Accordingly, to improve dose measurement accuracy, room temperature was measured and entered into the manufacturer’s acquisition software before each PSD probe measurement was taken.…”
Section: Methodsmentioning
confidence: 99%